The Influence of Piriform Recess Instillation with Lidocaine Before Bronchoscopy on Post-General Anesthesia Cough: A Randomized Controlled Trial - Min K; Wang Y; Feng D; Jin T; Zhu W; Duan R; Lv X (Dove Medical Press, 2024)
Keting Min,* Yu Wang,* Di Feng,* Tian Jin, Wanli Zhu, Ruowang Duan, Xin Lv Department of Anesthesiology, Shanghai Pulmonary Hospital, School of Medicine, Tongji University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin Lv; Ruowang Duan, Department of Anesthesiology, Shanghai Pulmonary Hospital, School of Medicine, Tongji University, 507 Zhengmin Road, Shanghai, 200032, People's Republic of China, Tel +8613661869972 ; +8618019713255, Email xinlv@tongji.edu.cn; duanruowang@163.comBackground and Importance: Postoperative cough is a common complication of general anesthesia after bronchoscopy. The aim of the present study was to determine the safety profile and efficacy of piriform recess instillation with lidocaine in reducing the incidence of coughing.Objective: To what extent could piriform recess instillation with lidocaine decrease the incidence of cough at 10min after extubation?Outcome Measures and Analysis: Eighty-eight consecutive patients were equally randomized to a lidocaine group receiving piriform recess instillation with 2mL 2% lidocaine, and a normal saline group receiving piriform recess instillation with 2mL saline. The primary outcome was the incidence of cough after extubation, and the secondary outcomes were throat score at 10 min and 6 h after extubation assessed by the numerical rating scale, cough severity at 10 min and 6 h after extubation assessed by the Visual Analog Scale (VAS), 24 h 40-item Quality of Recovery Score (QoR-40), and subject-rated satisfaction score on a VAS.Main Results: Compared with saline group, the incidence of cough in lidocaine group was significantly lower (63.6% vs 86.4%, P=0.014). The sore throat score at 10 min after extubation was significantly lower (0[0,0] vs 1[0,2], P< 0.001). The subject-rated overall anesthesia satisfaction score was significantly higher (84.8[± 6.2] vs 76.6[± 8.6], P< 0.001). The severity of cough at 10 min after extubation was significantly lower (Mild: 36.4% vs 11.4%, P=0.006; Severe: 9.1% vs 43.2%, P< 0.001). There was no significant difference in the sore throat score at 6 h after extubation, severity of cough at 6 h after extubation, or QoR-40 at 24 h after extubation between the two groups.Conclusion: Piriform recess instillation with lidocaine before bronchoscopy is a simple and effective method for reducing early cough intensity and alleviating early sore throat. At 6 hours, there were no differences observed between the groups.Clinical Trial Registration: Chinese Clinical Trial Registry (identifier: ChiCTR2200067087).Keywords: piriform recess, lidocaine, general anesthesia, cough, bronchoscopy